Movilidad social y experiencias reflexivas: procesos de hibridación en trayectorias de clase - Muñiz Terra, Leticia Magalí; Ambort, María Eugenia (El Colegio de México, 2023)
In this article, we analyzed social reproduction and mobility through an analysis of class trajectories. We used twenty-seven biographical interviews conducted within the framework of qualitative research on the labor and educational trajectories of social actors from various social classes in Argentina. The findings suggest that in their trajectories, social actors relate differently to the material, social, cultural, and symbolic capitals handed down by or available in their families. The way the appropriation, resignification, distancing, or abandonment of these capitals are linked to the opportunities arising from the macrosocial context and contingent aspects leads to hybridization.